Servicecape Management Analysis of Borma Supermarket Dago, Indonesia - Saputra, Niki Lili (Journal of Business and Management, 2012)
Borma Supermarket is a family owned supermarket business that is established in 1977. Currently the management of Borma supermarket feels that they are not as competitive as their competitor and want to improve their performance which can be done through improving the servicescape aspects of the store. A good servicescape management that makes a place comfortable for either customers and employee will benefit the company in many ways. The paper will focus on the perception of the customers toward the servicescape elements that currently exist in the supermarket. Borma servicescape is important because good servicescape will attract more customers. The objective of the paper is to know what is the gap that currently happens between the existing store servicescape quality with the perception of the customers in order to create a superior servicescape quality. From known gap, the management will know what the customers think about the servicescape of the store and able to make an improvement according to the customers opinion. The finding shows that most of the customers agreed that the servicescape quality is acceptable. In order to be more competitive in the supermarket business, Borma management could improve servicescape condition to increase customers’ satisfaction level. The survey indicated that several servicescape elements are poor so management must work it out to better one. Keywords : serviscape, retail store, customer perception, supermarket